2017
DOI: 10.1109/tap.2016.2630727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using Resistive Elements for Wideband Isolation Improvement

Abstract: Abstract-Improving the isolation between antenna elements in compact arrays has been a major focus of recent research. In this paper, we present ideas to improve the wideband isolation between closely spaced antennas. We do this by connecting lumped lossy (resistive) elements between the antenna feeds. A simple analytical expression is provided to compute the impact of resistive elements on efficiency to analyse the power lost in the resistive element. Three configurations of decoupling circuits are designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Passive decoupling networks that cancel the electromagnetic admittance between the antenna ports [23,29,32] and passive neutralization lines between antennas that create a cancelling signal path [22] have been used for isolation improvement between two antennas. However, their implementation complexity becomes increasingly prohibitive when more transmit and receive antennas are required.…”
Section: Antenna Decoupling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive decoupling networks that cancel the electromagnetic admittance between the antenna ports [23,29,32] and passive neutralization lines between antennas that create a cancelling signal path [22] have been used for isolation improvement between two antennas. However, their implementation complexity becomes increasingly prohibitive when more transmit and receive antennas are required.…”
Section: Antenna Decoupling Methodsmentioning
confidence: 99%
“…Increasing the electromagnetic isolation between the transmitting and receiving antenna [19][20][21][22][23][24][25][26][27][28] 2. Adding cancellation circuits to cancel the self-interference in the analog stages of the transmitter and the receiver [23,[29][30][31][32] 3. Using digital cancellation algorithms in the digital baseband of the receiver [18,31,33] The research in this dissertation concentrates on decreasing the selfinterference in the antenna domain, i.e., increasing the electromagnetic isolation between the receiving and transmitting antennas.…”
Section: The Mobile Networkmentioning
confidence: 99%
“…After implementing the design flow for objectives defined in (8) is the wavelength at center frequency of the operation band. The optimized fragment-type isolation structure is shown in Fig.…”
Section: Design Of the Bow-tie Mimo Antennamentioning
confidence: 99%
“…Different structures have been applied to suppress mutual coupling between MIMO antennas. By using parasitic elements [5], neutralization lines [6], decoupling networks [7], coupled resonator decoupling networks [8], defected ground structures [9], and electromagnetic band-gap structures [10], surface current or surface waves were suppressed to lower mutual coupling. These designs achieved isolation around 20dB within a relative bandwidth of about 11% for MIMO antennas.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the required load can be made purely reactive by tuning the antenna elements. A typical method to describe the mutual coupling has been to derive a circuit model for the antenna system and then creating an additional path of coupling which neutralizes the original mutual admittance between the antennas [6], [7].…”
Section: Introductionmentioning
confidence: 99%